Pengaruh Struktur Kepemilikan Sebagai Mekanisme Corporate Governance terhadap Kinerja Perbankan - Yeterina Widi Nugrahanti; Shella Novia (Jurnal Manajemen Maranatha, 2012)
The purpose of this study is to measure the ownership structure as a corporate governance mechanism on financial performance in the banking sector. Independent variables used in this study is the ownership structure that consists of foreign ownership, government ownership, institutional ownership, and managerialownership. Than, banks performance is measured by ROA (Return On Assets). The control variable used in this study is firm size. This study uses the general banking company which is listed in Indonesia Stock Exchange (BEI) in the period 2009-2010. By purposive sampling, this study obtained 27 samples company. The research period is two years, so 54 (27 samples x 2 years) annual reports will be used in this research. For testing hypothesis, this study uses multiple regressionanalysis by spss 16. The results showed that institutional ownership and firm size have positif significant effect to banks performance. While, foreign ownership, governmental ownership, and managerial ownership have no influence to banks performance.